Inguinal hernia repair by rectus abdominis sheath plasty: Is Berger’s operation still valid? - Ribero, Gustavo; Sauto, Sergio; Derbogosián, A.; Caviglia, L. (Cirugía del Uruguay, 1997)
The authors present preliminary experience in herniary repair by means of autoplastia with rectus abdominis sheath. lt is a modified version of Berger's operation, which was applied in 14 cases with good results. Authors provide technical details, its basis, indication and results. They arrive to the conclusion that autoplastia of the Berger type is an interesting alternative in the treatment of inguinal hernia and its recidives; it is a strain-free technique which can be associated to other inguinal hernia correction procedures.